Benefits and Risks of Community Use E-Wallet as an Alternative Transaction - Fani Aristianti; Muhammad Iqbal Phase (Yayasan Adra Karima Hubbi, 2024)
This study was conducted to determine the benefits and risks of people using E-wallets as an alternative transaction. E-wallets have become one of the popular payment methods in this digital era. The use of e-wallets offers various benefits, including ease and speed in making transactions, 24/7 accessibility, and the potential for better financial management through automatic recording. In addition, e-wallets are often equipped with promotions and discounts, attracting users to switch from traditional payment methods. However, there are also risks that need to be considered. The security of personal and financial data is a major concern, due to the potential for identity theft and online fraud. This study uses a library research method, namely a method of collecting data by understanding and studying theories from various literatures related to the research. In addition, dependence on technology can cause problems when the system is disrupted or when users do not have access to the internet. Therefore, it is important for users to understand both the benefits and risks associated with using e-wallets, and to take the necessary security measures in making transactions.